Using 3D-reconstruction to analyse typical growth trends of the maxillary sinus in children. (November 2020) - Lee, Sophie; Fernandez, Justin Wade; Mahadevan, Murali; Tarr, Gregory; Mirjalili, Ali
Abstract: Objectives: There remains a lack of consistent evidence surrounding the developmental anatomy of the maxillary sinus (MS), despite its clinical significance in radiological interpretation and surgical intervention. Our aim was to analyse the typical growth trends of the MS throughout development, to better understand its morphological transformation from birth until late adolescence. Methods: Computed Tomography (CT) scans of individuals aged 0–18 years within the Auckland District Health Board region in New Zealand were examined retrospectively. Sixty-five patients were selected for the study after careful review of criteria. Manual 3D-reconstruction was utilised to replicate the MS from CT images and the mean changes in size, volume and shape with increasing age were analysed. Principal component analysis (PCA) was performed to statistically calculate the mean 3D shapes of the MS in each age group and analyse the independent modes of variation evident in sinus morphology between individuals of each age category. Results: At 0–1 years of age, mean MS size was 1.03 × 1.82 × 1.27 cm (width, length, height) with a mean volume of 0.81 cm 3 . By 16–18 years, mean size increased to 3.39 × 4.30 × 4.63 cm and mean volume became 21.63 cm 3 . Growth increased linearly but most rapid expansion occurred in the first 4–5 years of life. No significant differences were observed between males and females or right and left sides. Sinus morphology gradually progressed throughout the course of growth from an ellipsoidal structure at its rudimentary phase to a pyramidal shape when fully matured. PCA revealed that within younger age groups significant variation was observed in MS size, while older age groups had relatively less size variation but increased variability in 3D shape. Conclusions: The results of this study can be used as a reference for typical MS growth in healthy children and as a basis to study how disease or surgical intervention may influence sinus development in children.